A retrospective study of theophylline-based therapy with tracheal collapse in small-breed dogs: 47 cases (2013–2017) - Jeung, So-Young (J Vet Sci, 2019)
Theophylline acts as a bronchodilator and has an anti-inflammatory effect. In addition, theophylline can be applied in patients where there are concerns regarding the side-effects of corticosteroids. This retrospective case series evaluated theophylline-based therapy in tracheal collapse (TC) canine patients. Forty-seven dogs with TC that received theophylline-based therapy during 2013–2017 were investigated. A fluoroscopic examination was performed to diagnose and grade TC. Theophylline was prescribed (7.5–30 mg/kg PO q12h) and the theophylline serum concentrations were measured. Coughing was assessed using a coughing scoring scale. The mean coughing score decreased after the theophylline-based therapy compared with that observed before treatment. Clinical improvements were observed in 46/47 patients (97.9%). As the intrathoracic TC grading increased, the final theophylline dosage also increased (p value 0.019). The symptom-free period (SFP) with therapy was 189.7 ± 194.45 days (range, 0–720 days) and there was no statistically significant correlation between the SFP and age, sex, or TC grade on fluoroscopy. Although theophylline has generally been used as a third-line treatment, it was used as the main treatment in this study and most patients showed improvements. Dogs have a wider therapeutic index of serum concentrations than humans, and any undesirable effects were easily overcome. With further research, this therapy may prove to be a useful approach, but its safety for long-term use in the treatment of canine TC patients needs to be established.